Psychological Violence in the Workplace and the Emergence of Reactive Disorders - Njifon Nsangou Hassan; Chounna Margarette; Martial Nguegno Fouadjo; Gustave Adolphe Messanga (Nusantara Journal of Behavioral and Social Science, 2026)
Research on psychological violence in the workplace generally focuses on the emergence of specific disorders, and less often on a broader nosographic framework. This study, which investigates experiences of psychological violence at work, examines reactive disorders associated with such violence, the psychosocial risk factors involved, and the underlying psychological processes. Using a qualitative multiple-case study design with embedded clinical diagnostic assessment, data were collected through the french versions of the Leymann Inventory of Psychological Terror (LIPT), the Mini International Neuropsychiatric Interview (MINI), and a semi-structured interview guide. The findings suggest an association between workplace psychological violence and reactive anxiety disorders, mood disorders, and peritraumatic stress symptoms. These disorders were linked to experiences of separation, inter-individual professional conflicts, work-related stress issues, and verbal threats. The psychological processes involved include vulnerabilities related to negative perceptions of the work environment, anxiety-laden autobiographical memories, and intrusive re-experiencing of workplace violence. This study contributes to the literature by situating workplace psychological violence within a broader nosographic framework of reactive disorders rather than focusing on isolated diagnoses. However, the small sample size and case-study design limit the generalizability of the findings. The results underscore the need to establish independent and confidential listening and psychological support units to assist workers.   Abstrak: Penelitian mengenai kekerasan psikologis di tempat kerja umumnya berfokus pada munculnya gangguan-gangguan tertentu, dan lebih jarang menempatkannya dalam kerangka nosografis yang lebih luas. Studi ini, yang menelaah pengalaman kekerasan psikologis di tempat kerja, mengkaji gangguan reaktif yang terkait dengan kekerasan tersebut, faktor-faktor risiko psikososial yang terlibat, serta proses psikologis yang mendasarinya. Dengan menggunakan desain penelitian kualitatif studi multi-kasus yang dilengkapi dengan asesmen diagnostik klinis, data dikumpulkan melalui versi bahasa Prancis dari Leymann Inventory of Psychological Terror (LIPT), Mini International Neuropsychiatric Interview (MINI), serta panduan wawancara semi-terstruktur. Hasil penelitian menunjukkan adanya hubungan antara kekerasan psikologis di tempat kerja dengan gangguan kecemasan reaktif, gangguan suasana hati, dan gejala stres peritraumatik. Gangguan-gangguan ini berkaitan dengan pengalaman perpisahan, konflik profesional antarindividu, masalah stres terkait pekerjaan, serta ancaman verbal. Proses psikologis yang terlibat meliputi kerentanan yang berkaitan dengan persepsi negatif terhadap lingkungan kerja, ingatan autobiografis yang sarat kecemasan, serta pengalaman ulang intrusif terhadap kekerasan di tempat kerja. Studi ini memberikan kontribusi terhadap literatur dengan menempatkan kekerasan psikologis di tempat kerja dalam kerangka nosografis gangguan reaktif yang lebih luas, alih-alih berfokus pada diagnosis yang terisolasi. Namun, ukuran sampel yang kecil dan desain studi kasus membatasi generalisasi temuan. Hasil penelitian ini menegaskan perlunya pembentukan unit pendengaran dan dukungan psikologis yang independen dan bersifat rahasia untuk membantu para pekerja